Increasing the efficiency of hyperthermic intraperitoneal chemotherapy (HIPEC) by combination with a photosensitive drug in pediatric rhabdomyosarcoma in an animal model. Issue 11 (12th July 2022) - Wagner, Benedikt R.; Adamus, Anna L.; Hempfling, Laura; Vahdad, Reza; Haap‐Hoff, Antje; Heinrich, Benedikt; Vázquez, Olalla; Jank, Paul; Denkert, Carsten; Seitz, Guido
Abstract: Background: Cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) is an option in advanced peritoneal sarcomatosis. Nevertheless, CRS and HIPEC are not successful in all patients. An enhancement of HIPEC using photodynamic therapy (PDT) might be beneficial. Therefore, a combination of the photosensitizer hypericin (HYP) with HIPEC was evaluated in an animal model. Procedure: An established HIPEC animal model for rhabdomyosarcoma (NOD/LtSz‐scid IL2Rγnullmice, n = 80) was used. All groups received HYP (100 μg/200 μl) intraperitoneally with and without cisplatin‐based (30 or 60 mg/m 2 ) HIPEC (37°C or 42°C, for 60 minutes) (five groups, each n = 16). Peritoneal cancer index (PCI) was documented visually and by HYP‐based photodynamic diagnosis (PDD). HYP‐based PDT of the tumor was performed. Tissue samples were evaluated regarding proliferation (Ki‐67) and apoptosis (TUNEL). Results: HYP uptake was detected even in smallest tumor nodes (<1 mm) with improved tumor detection during PDD (PCI with PDD vs. PCI without PDD: 8.5 vs. 7, p < .001***). Apoptotic effects after PDT without HIPEC were limited to the tumor surface, whereas PDT after HIPEC (60 mg/m 2, 42°C) showed additional reduction of tumor proliferation in the top nine to 11 cell layers (50 μm). Conclusion: HYP as fluorescent photosensitizer offers an intraoperative diagnostic advantage detecting intraperitoneal tumor dissemination. The combination of HYP and cisplatin‐based HIPEC was feasible in vivo, showing enhanced effects on tumor proliferation and apoptosis induction across the tumor surface. Further studies combining HYP and HIPEC will follow to establish a clinical application.